Wedge resection vs. segmentectomy for lung cancer measuring ≤ 2 cm with consolidation tumor ratio > 0.25 - Isaka, Tetsuya; Nagashima, Takuya; Adachi, Hiroyuki; Narimatsu, Hiroto; Murakami, Kotaro; Shigefuku, Shunsuke; Kikunishi, Noritake; Shigeta, Naoko; Watabe, Kozue; Kudo, Yujin; Miyata, Yoshihiro; Okada, Morihito; et al. (Frontiers in Oncology, 2023)
Objectives We aimed to clarify the differences in prognosis between wedge resection and segmentectomy performed for cN0 non-small cell lung cancer (NSCLC) measuring ≤ 2 cm, with consolidation tumor ratio (CTR) > 0.25. Methods This multicenter study included 570 patients with cN0 NSCLC (tumor size ≤ 2 cm, CTR > 0.25) who underwent wedge resection (n = 244) and segmentectomy (n = 3 26) between January 2010 and December 2018. After propensity score matching (PSM, 1:1 method), 182 patients were matched for clinical characteristics (age, sex, laterality, smoking index, tumor size, CTR, carcinoembryonic antigen value, positron-emission tomography-documented maximum standardized uptake value, clinical stage, and tumor disappearance rate) and intergroup comparison of disease-free survival (DFS) and overall survival (OS). Using Gray’s test, an intergroup comparison of the cumulative incidence of lung cancer-specific mortality was performed. Results After PSM, similar DFS (5-year DFS, 79.9% vs. 87.1%, p = 0.103) and OS (5-year OS, 88.7% vs. 88.9%, p = 0.719) rates were observed in the wedge resection and segmentectomy groups. We observed no significant intergroup differences in lung cancer-specific mortality (5-year cumulative incidence: 4.6% vs. 3.5%; p = 0.235). Subgroup analysis indicated that neither wedge resection nor segmentectomy improved the DFS or OS in specific subgroups. Conclusions DFS, OS, and lung cancer-specific mortality were comparable between wedge resection and segmentectomy of cN0 NSCLC—tumor size ≤ 2 cm and CTR > 0.25. Large-scale prospective clinical trials are warranted to compare the prognoses of wedge resection and segmentectomy for these tumors.